Nurse leader training and strength-based coaching: Impact on leadership style and resiliency. Issue 10 (October 2021) - Spiva, LeeAnna; Hedenstrom, Lisa; Ballard, Nancy; Buitrago, Paola; Davis, Stephan; Hogue, Vicky; Box, Melissa; Taasoobshirazi, Gita; Case-Wirth, Jill
Abstract : Find out how one healthcare organization implemented a comprehensive training program, including strength-based coaching, to foster leadership competencies and skill development, promote the organization's resiliency program, and nurture personal wellness.